The Samson Option - Davies, Murray (London Harper Collins Publishers, 2000)
An Iraqi terrorist - himself under threat of a terrifying reprisal from Sadam Hussein - attempts to bring in to the UK a flask of unimaginably destructive bacteria. Set against the threat is a small team of experts, soldiers and spooks in Whitehall. But information is leaking, somehow.
Keywords: Terrorism -- Great Britain